Molecular dynamics study on evaporation of high-salinity wastewater droplet. (August 2022) - Zhan, Lingxiao; Chen, Heng; Zhou, Hao; Feng, Qianyuan; Gu, Liyan; Yang, Linjun; Sun, Zongkang
Highlights: Evaporation of wastewater droplets was studied by Molecular Dynamics Simulations. Influences of ambient temperature, droplet size, and components were considered. Ion-water interaction, weaker heat transfer, and higher sphericity retard evaporation rate. Nucleation and dehydration process was monitored by coordination number analysis. Divalent cations interact with ions and water molecules more actively. Abstract: Non-equilibrium molecular dynamics simulations (NEMD) are carried out to study the evaporation behaviors of high-salinity wastewater droplets in a high-temperature environment (>500 K). Detailed information on interfacial properties and evaporation characteristics of wastewater droplets containing multiple salts are monitored quantitatively for the first time. To investigate how ions and molecules interact with each other during evaporation, nucleation and growth of ions clusters and the dehydration process are studied by the coordination number analysis. The accuracy of the model is validated by the experimental results, and then effects of ambient temperatures, compositions, and initial sizes are considered. The results show that when the evaporation reaches the steady state in the 600 K ambience, the droplet evaporation rate of wastewater is much smaller than that of the pure water, which can be seen from the evaporation constant (5.58 × 10 −9 m 2 /s for pure water vs 4.60 × 10 −9 m 2 /s for wastewater). After this steady state, the evaporation rate for wastewater is reduced, during which nucleation of ion pairs and dehydration would occur. Ion-water interaction, smaller temperature difference between ambience and droplets, and higher sphericity contribute to the decline in the evaporation rate of wastewater. Nucleation trends of different ion pairs in wastewater vary significantly, and divalent cations (Mg 2+ and Ca 2+ ) play an important role in restricting the motions of water molecules and forming clusters, as shown in the higher average counter ion coordination number. Dehydration of the ions will not occur until most water molecules are evaporated, which is more difficult for divalent ions. Increasing thermostat temperature, decreasing total dissolved solids and decreasing initial sizes are conducive to accelerating the overall evaporation and nucleation rate. The research gives a better understanding of the microscopic mechanisms of wastewater droplet evaporation and further aids in the design and optimization of the thermal desalination process.